Enhanced Anti-Inflammatory Activity of Kaempferia galanga Extract by Solid Self-Nanoemulsifying Drug Delivery System and Its Development in Fast Disintegrating Tablet - Latifani, Salma; Fitriani, Annisa nur; Paniroy; Maesayani, Kadek Sanitha; Freddy, Juan; Adianingsih, Oktavia Rahayu (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
The increasing global incidence of osteoarthritis (OA) emphasizes the need for effective treatments, particularly for the elderly. Conventional OA treatments pose administration challenges, leading to patient discomfort due to difficulties in administration. Herbal formulations offer an alternative to mitigate these issues. Kaempferia galanga (KG) contains ethyl p-methoxycinnamate, a compound displaying anti-inflammatory properties that hold promise for OA treatment. This study explores the formulation of a solid self-nanoemulsifying drug delivery system (S-SNEDDS) of Kaempferia galanga extract (KGE) and evaluates its anti inflammatory efficacy, subsequently developing it into a fast disintegrating tablet (FDT) dosage form. Initially, a liquid SNEDDS (L-SNEDDS) was prepared with varying surfactant and co surfactant concentrations. The optimal formula of L-SNEDDS (FL2) using tween 80: cremophor RH 40: PEG 400 in a ratio of 1:1:2 demonstrated favorable characteristics, including transmittance of 86.93 ± 1.16%, emulsification time of 28 ± 2.65 s, particle size of 27.79 ± 2.00 nm, PDI of 0.21 ± 0.014, and zeta potential of -12.57 mV. FL2 was solidified using aerosil 200 to produce S-SNEDDS and tested for anti-inflammatory efficacy in vivo using a carrageenan induced rat model. Results showed enhanced anti-inflammatory efficacy of KGE via S-SNEDDS, marked by reduced edema volume. Afterward, FDT S-SNEDDS were prepared using the direct compression method by comparing different types of superdisintegrants. The formulation using the combination of crospovidone and croscarmellose sodium (FT2) demonstrated excellent flow properties, tablet disintegration time of 63 s, wetting time of 34.01 ± 7.87 s, friability of 0.19%, and hardness of 3.53 ± 6.16 kg/cm2. The dissolution test indicated a better dissolution profile for FT2 compared to other formulations. In conclusion, this research presents the potential of FDT S-SNEDDS as a promising drug delivery system for enhancing the therapeutic effects of Kaempferia galanga extract in treating inflammatory conditions such as osteoarthritis.